Research progress on the mechanism of beta-cell apoptosis in type 2 diabetes mellitus - You, SuFang; Zheng, JingYi; Chen, YuPing; Huang, HuiBin (Frontiers in Endocrinology, 2022)
Type 2 diabetes mellitus(T2DM) is regarded as one of the most severe chronic metabolic diseases worldwide, which poses a great threat to human safety and health. The main feature of T2DM is the deterioration of pancreatic beta-cell function. More and more studies have shown that the decline of pancreatic beta-cell function in T2DM can be attributable to beta-cell apoptosis, but the exact mechanisms of beta-cell apoptosis in T2DM are not yet fully clarified. Therefore, in this review, we will focus on the current status and progress of research on the mechanism of pancreatic beta-cell apoptosis in T2DM, to provide new ideas for T2DM treatment strategies.